The Role of Analytical Convergence in Student Learning: Mapping Cognitive Strategies in Higher Education Assessment - Moses Adeleke Adeoye; Motunrayo Elizabeth Olude (Universitas Sebelas Maret, 2025)
This paper addresses a critical yet under-theorised issue in higher education assessment: the limited recognition and evaluation of analytical convergence—students’ ability to synthesise diverse perspectives into coherent, epistemically grounded conclusions. Despite widespread adoption of outcomes-based education and constructive alignment frameworks, current assessment practices often reward structural clarity and content accuracy over cognitive integration, thus undervaluing a key indicator of deep learning. Grounded in a conceptual, qualitative methodology informed by interpretivism and constructivist epistemology, the study synthesises insights from educational psychology, curriculum theory and assessment studies. It draws on metacognitive theory, cognitive load theory, and models of constructive alignment to map the cognitive processes underlying convergence—such as abstraction, epistemic triangulation, and conceptual reframing. Findings indicate that convergence often emerges in student work through reflective synthesis and problem redefinition but remains obscured by rubrics and feedback mechanisms that privilege surface-level indicators. The paper identifies task types and pedagogical strategies—such as open-ended inquiry, comparative critique, and scaffolded reflection—that enable intellectual integration. This study contributes to the re-theorisation of assessment by articulating convergence as a developmental, assessable cognitive process. It addresses a key gap in the literature by operationalising convergence as both a learning outcome and an evaluative construct. The paper concludes with implications for educators, curriculum designers, and policymakers, calling for rubric reform, metacognitive scaffolding, and alignment of assessment with the intellectual demands of contemporary higher education.